Business intelligence supporting the teaching-learning process - Piedade, Maria Beatriz (2009)
One of the activities usually pointed out as crucial to promote the students’ success is the closely monitoring of the students’ academic activities related with the teaching-learning process. Although important this activity does not take place in many higher education institutions. To support this complex process an adequate, conceptual and technological support is needed. In this sense, it is presented in this paper a Student Relationship Management (SRM) system. The SRM system supports the SRM concept and practice and is based in a Business Intelligence infrastructure. To demonstrate the SRM system relevance in the process of acquisition of knowledge about the students and theirs academic behaviour, in the support of the decision-making associated to the teaching-learning process and in the automatic interaction with the students, it is presented an application case, which was carried out in a real context.